Opportunities for Self-Development in Sports and Recreation for PJKR/PJSD UNNES Students Through Outdoor Education Courses - Ady Tia Susanto; Imam Santosa Ciptaning Wahyu W (Indonesian Journal for Physical Education and Sport, 2025)
This study aims to provide an overview of these opportunities through out-of-class education courses, as a guide for students in developing themselves in this field. This study used a descriptive qualitative method to understand the phenomenon at the Faculty of Sports Science, Universitas Negeri Semarang. The respondents were PJKR and PJSD alumni who had attended out-of-class education courses, to gain in-depth insights into opportunities to develop their potential in the field of sport recreation. The results showed that PJKR and PJSD students at Semarang State University have a good understanding of the opportunities in sport recreation, although there are still challenges. They are aware of the importance of safety and early treatment in outdoor activities. The study also found students' high interest in entrepreneurship in this field, although they still need guidance. These findings indicate students' readiness for a career in sport and recreation, as well as the importance of curriculum development that is more in line with industry needs. The conclusion of this study shows that PJKR and PJSD alumni of Semarang State University have a high awareness of career opportunities in the field of sport recreation, such as becoming educators, coaches, massage therapists, or entrepreneurs. The knowledge gained during college is considered very valuable. The study also emphasized the importance of understanding safety in outdoor activities and the need for support for entrepreneurship.